Longitudinal association between handgrip strength, gait speed and risk of serious falls in a community-dwelling older population - Pham, Thao; McNeil, John J.; Barker, Anna L.; Orchard, Suzanne G.; Newman, Anne B.; Robb, Catherine; Ernst, Michael E.; Espinoza, Sara; Woods, Robyn L.; Nelson, Mark R.; Beilin, Lawrence; Hussain, Sultana Monira (PloS one, 2023)
Both grip strength and gait speed can be used as markers of muscle function, however, no previous study has examined them in the same population with respect to risk of falls. In this prospective cohort study, utilising data from the ASPirin in Reducing Events in the Elderly (ASPREE) trial and ASPREE-Fracture substudy, we analysed the association of grip strength and gait speed and serious falls in healthy older adults. Grip strength was measured using a handheld dynamometer and gait speed from 3-metre timed walks. Serious falls were confined to those involving hospital presentation. Cox regression was used to calculate hazard ratios (HR) and 95% confidence intervals (CI) for associations with falls. Over an average of 4.0±1.3 years, amongst 16,445 participants, 1,533 had at least one serious fall. After adjustment for age, sex, physical activity, body mass index, Short Form 12 (state of health), chronic kidney disease, polypharmacy and aspirin, each standard deviation (SD) lower grip strength was associated with 27% (HR 1.27, 95% CI 1.17-1.38) higher risk of falls. The results remained the same for males and females. There was a dose-response relationship in the association between grip strength and falls risk. The higher risk of falls was observed in males in all body mass index (BMI) categories, but only in obese females. The association between gait speed and falls risk was weaker than the association between grip strength and falls risk. All males and only obese females with low grip strength appear to be at the greatest risk of serious falls. These findings may assist in early identification of falls.